As universidades confessionais brasileiras e as reformas da educação superior da década de 1990 - Tavares, Sérgio Marcus Nogueira (Universidade Federal de São Carlos, 2012)
This study has as an objective to examine the consequences of higher education amendments and the institutional transformations it has been suffering in this scenery. It was collected data from four institutions that act in the state of São Paulo, from which two are confessional universities with a historical presence on this sector and the other two are from the business segment that came from the educational amendments and have expanded from it. It has been used the concepts of substantive rationality and formal rationality of economic ends from Max Weber in order to analyze the researched data from the universities, gathered as the following: the concept of university and the academic, management, the economic-financier concept and its relation with society. The confessional universities have became after the amendments, an alternative in crisis, in which the challenge is, from one side, to survive without surrender to the market s logic and keep its identity with no disguises, and on the other side, being acknowledged as such by public policies, in a way of assuring the conditions to act in the search of quality and relevance of Brazilian s superior education.
Keywords: Ensino superior; Universidades e faculdades; Reformas do estado; Racionalidade; Educação superior; Universidade Confessional; Reformas; Higher education; Confessional University; Amendments; Rationality; CIENCIAS HUMANAS::EDUCACAO